Answer:
Solution: x³ + 3x² + 3x + 1
Step-by-step explanation:
Take a look at the following Pascal's Triangle:
(x + y)⁰ = 1
(x + y)¹ = 1x + 1y
(x + y)² = 1x² + 2xy + 1y²
(x + y)³ = 1x³ + 3x²y + 3xy² + 1y³
(x + y)⁴ = 1x⁴ + 4x³ + 6x²y² + 4xy³ + 1y⁴
As you can see our binomial is '(x + 1)³.' Therefore we expand the expression with respect to the third row in the Pascal's Triangle, (x + y)³ = 1x³ + 3x²y + 3xy² + 1y³. The procedure would be as follows:
(x + 1)³ = 1x³ + 3(x)²1 + 3x(1)² + 1(1)³ = x³ + 3x² + 3x + 1
Answer:
option a 21 is the right answer
Step-by-step explanation:
7/12.36
12 into 3 is 36
so 12 1's are and 12 3's are
now it'll become 7 into 3
which is 21
therefore 21 is the answer
a + b + c = 30 ;
a = 6c ;
a = 2b ;
Then, c = a / 6 and b = a / 2 ;
a / 6 + a / 2 + a = 30 ;
a / 6 + 3a / 6 + 6a / 6 = 180 / 6 ;
10a = 180 ;
a = 18 ;
b = 9 ;
c = 3.
Good luck !
8 is the answer because you count up from the lower number
these inequalities can be solved just like equations
a. x - 7 > 25
+ 7 +7 x > 32the number line would have a filled in circle at 32 with an arrow pointing to the rightb. x - 8 < 5+8 +8x < 13 the number line would have an empty circle at 13 with an arrow pointing to the leftc.x + 11 > 23 - 11 - 11x > 12the number line would have an empty circle at 12 with an arrow pointing to the rightd. x + 12 < 6 - 12 - 12 x < -6the number line would have a filled in circle at -6 with an arrow pointing to the lefta. 21 < x + 18 -18 -18 3 < xx > 3b. 16 < x - 7 + 7 + 7 23 < x x > 23c. 12 > x - 7 + 7 + 7 19 > x x < 19d. 29 < x + 53 - 53 - 53 -24 < x x > -24e. 15 > x + 19 -19 -19 -4 > x x < -4f. 35 > x - 8 +8 +8 43 > x x < 43g. -6 < x - 18 +18 +18 12 < x x > 12h. -15 < x - 2 + 2 +2 -13 < x x > -13